2014
DOI: 10.1039/c4ra08308c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiation effect on extractability of an isobutyl-BTP/ionic liquid system: quantitative analysis and identification of radiolytic products

Abstract: Approaches were established for assessing the influence of radiation effect on the extractability of the 2,6-di(5,6-diisobutyl-1,2,4-triazin-3-yl)pyridine (isobutyl-BTP)/1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([C2mim][NTf2]) extraction system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…13 Moreover, it has been, recently, reported that the R-BTP based extraction system is more radiation resistant in RTIL medium as compared to that in molecular solvents. 14 It is, therefore, important to explore the use of RTILs for process applications using radioactive elements with better recycling possibilities. Cocalia et al 15 have observed similar extraction and complexation behaviour of various actinide and lanthanide ions with dialkyl phosphoric and phosphinic acids in RTIL and molecular diluents.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, it has been, recently, reported that the R-BTP based extraction system is more radiation resistant in RTIL medium as compared to that in molecular solvents. 14 It is, therefore, important to explore the use of RTILs for process applications using radioactive elements with better recycling possibilities. Cocalia et al 15 have observed similar extraction and complexation behaviour of various actinide and lanthanide ions with dialkyl phosphoric and phosphinic acids in RTIL and molecular diluents.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of liquid–liquid extraction using BTP derivatives, radiation-induced degradation of the extractant is mainly facilitated by the diluents . The degradation of i Bu-BTP was found to be much higher in the 1-octanol medium than in the room-temperature ionic-liquid (RTIL) medium, as 1-octanol produced free radicals more easily under gamma irradiation .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of liquid−liquid extraction using BTP derivatives, radiation-induced degradation of the extractant is mainly facilitated by the diluents. 49 The degradation of iBu-BTP was found to be much higher in the 1-octanol medium than in the room-temperature ionic-liquid (RTIL) medium, as 1-octanol produced free radicals more easily under gamma irradiation. 47 Even with the hydrophilic BTP derivative (SO 3 PhBTP), the separation behavior deteriorated significantly at a radiation dose of 300 kGy beyond which the extraction of americium was found to have increased by an order of 2.…”
Section: Stability Of the Materialmentioning
confidence: 99%
“…The results showed that [C 2 mim][NTf 2 ] provided radioprotection for isobutyl-BTP comparing 1-octanolas a conjugated system was formed between isobutyl-BTP and imidazoliumcation. 28,29 However, as far as our best knowledge is concerned, few work focused on the radiation effect on the extractability of TODGA in RTILs.…”
Section: Introductionmentioning
confidence: 99%